Evaluation of Naso-facial proportion of the Face and Their Correlation in Bangladeshi Buddhist Rakhain Ethnic Males - Iqbal, Mohammed; Nahar, Nazmun; Rahman, Kazi Md. Shahidur; Rahman, Md Zamilur; Uddin, SK Amin Mohi; Alam, Mohammed Safiul; Alam, Urmee (Journal of Current and Advance Medical Research, 2022)
Background: The face and nasal dimensions are most important cephalometric parameters describing human morphology. Nose is the most important aesthetic unit of face. There is wide variation in size and shape of nose and face due to ethnic influences. Objective: The purpose of the present study was to evaluate the naso-facial proportion of the face and their correlation in adult healthy Bangladeshi Buddhist Rakhain Ethnic males. Methodology: This cross-sectional observational study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from January 2011 to December 2011 for a period of one (01) year. Adult Healthy Bangladeshi Buddhist Rakhain males with the age group of 18 to 30 years were included as study population. Results: This study shows mean of nose width was 41.16 (±3.03) and mean of ¼ face width was 34.80(±1.70). This study shows nose width was 41.16 (±3.03) and ¼ face width was 34.80(±1.70). Conclusion: It was observed that nose width was significantly wider than ¼ of face width in the adult healthy Bangladeshi Buddhist Rakhain. This parameter was the importance of using patients as observers, as well as clinicians, in facial attractiveness research. Journal of Current and Advance Medical Research, January 2022;9(1):32-35